Study on the physicochemical indexes, nutritional quality, and flavor compounds of Trichiurus lepturus from three representative origins for geographical traceability - Wang, Shitong; Wang, Pingya; Cui, Yiwei; Lu, Weibo; Shen, Xuewei; Zheng, Huimin; Xue, Jing; Chen, Kang; Zhao, Qiaoling; Shen, Qing (Frontiers in Nutrition, 2022)
Trichiurus lepturus (hairtail) is an important economic component of China’s marine fishing industry. However, due to the difficulty in identifying the appearance of hairtail from different geographical distributions, hairtails with geographical indication trademarks were imitated by general varieties. In this study, the texture characteristics, color, basic nutrients, amino acids, mineral, fatty acids, and volatile flavor substances were used as indicators for multivariate statistical analysis to determine whether three origins of hairtails from the habitats of Zhoushan (East China Sea, T.Z), Hainan (South China Sea, T.N), and Qingdao (Yellow Sea, T.Q) in the market could be distinguished. The findings revealed that there were significant differences in amino acids composition, mineral composition, fatty acid composition in lipids, and volatile flavor substances among the hairtails of three origins (P < 0.05), but no differences in color, texture, protein content. T.Z had moisture, crude fat, essential amino acids (EAA), flavor amino acids (FAA), unsaturated fatty acids (UFA), and docosahexaenoic acids and dicosapentaenoic acids (ΣEPA + DHA) contents of 74.33, 5.4%, 58.25 mg⋅g–1, 46.20 mg⋅g–1, 66.84 and 19.38%, respectively, and the contents of volatile alcohols, aldehydes and ketones were 7.44, 5.30, and 5.38%, respectively. T.N contains moisture, crude fat, EAA, FAA, UFA and ΣEPA + DHA as 77.69, 2.38%, 64.76 mg⋅g–1, 52.44 mg⋅g–1, 65.52 and 29.45%, respectively, and the contents of volatile alcohols, aldehydes and ketones as 3.21, 8.92, and 10.98%, respectively. T.Q had the contents of moisture, crude fat, EAA, FAA, UFA, and ΣEPA + DHA 79.69, 1.43%, 60.9 mg⋅g–1, and 49.42 mg⋅g–1, respectively. The contents of unsaturated fatty acid and ΣEPA + DHA were 63.75 and 26.12%, respectively, while the volatile alcohols, aldehydes, and ketones were 5.14, 5.99, and 7.85%, respectively. Partial least squares-discriminant analysis (PLS-DA) multivariate statistical analysis showed that volatile flavor compounds could be used as the most ideal indicators for tracing the source of hairtail. In conclusion, the findings of this study can distinguish the three hairtail origins using some basic indicators, providing ideas for hairtail geographical identification.